Altered expression profile of circular RNAs in conjunctival melanoma. (May 2019) - Shang, Qingfeng; Li, Yongyun; Wang, Huixue; Ge, Shengfang; Jia, Renbing
Aim: We aimed to explore the roles of circular RNA (circRNA) in conjunctival melanoma.Materials & methods : The altered circRNAs were identified by RNA sequencing. The function of one circRNA, circMTUS1, was explored by several experiments in conjunctival melanoma. Bioinformatic analyses and an RNA immunoprecipitation assay were performed to further study the downstream mechanism of circMTUS1.Results : We identified 9300 different circRNAs in conjunctival melanoma tissues compared with adjacent normal tissues. CircMTUS1 was upregulated in conjunctival melanoma. Silencing of circMTUS1 inhibited conjunctival melanoma proliferation in vitro and in vivo . CircMTUS1 may serve as an oncogene by binding to hsa-miR-622 and hsa-miR-1208 to regulate several tumor-related pathways.Conclusion: We demonstrated that circMTUS1 may serve as an oncogene to promote tumor proliferation.